Innovations in Wind Power Generation Devices (WPP) That Saves Production Costs - Steven Johny Runtuwene; Rinna Yuanita Kasenda; Natalia Artha Malau; Dheandro Dheandro; Arya Matadjang; Christo Waas; Angel Sindar; Joshua Ngantung; Andro Tatemba; Joshua Maliatja (Interdisciplinary Journal of Advanced Research and Innovation, 2025)
The innovation of Wind Power Plants in order to save costs in terms of production compared to Conventional Wind Power Plants¸ power plants that we usually encounter are in the form of windmills whose task is the same, namely using the wind as the driving force, models such as windmills that usually cost a lot, so the innovation created by SkySails Group is expected to be the beginning for other inventions, but certainly not to replace existing Wind Power Plants.  This research employs a comprehensive methodology to explore the feasibility and advantages of kite-based wind farm systems, focusing on using towers as kite anchoring points. The result by Airborne Wind Europe, found that a wind farm containing a kite wind farm generating 50 megawatts of electricity would use only 913 metric tons of material over a 20-year period. This is far less than a conventional wind farm that requires 2,868 metric tons of material. This certainly supports sustainable green energy.